Analisis Sistem Informasi Customer Relationship Management Berbasis Web Pada PT. INOVATIF TEKNIK MESINDO: ID - Sari, Herva Emilda; Prasetiawati, Rizka (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
This study is based on the problems in the case study of PT INOVATIF TEKNIK MESINDO namely the increase in the number of customers that are not followed by the renewal of the customer data management system makes the existing performance ineffective and inefficient. Therefore, the purpose of this research is to build an information system regarding the matter concerned with the customer so as to facilitate the company in reading the desires and habits of the customer through activities that occur in the CRM (Customer Relationship Management) system and can make a decision to improve quality and company quantity. In this study there are 3 (three) main problems, 5 (five) research objectives, 4 (four) research benefits. Also explained the relevant data collection methods including the observation method, UML (Unified Modelling Language) to describe the running system and the design of the prototype to be built. Keywords : Companies, Information Systems, Customer Relationship Management, Unified Modelling Language